Public perception of the Kamenná District - Sofie Pokorná; Klára Francová; Nikola Číhalová (Acta Polytechnica CTU Proceedings)
The article describes the emergence of emergency and workers’ colonies in the city of Brno from the beginning of the 20s of the 20th century. It also briefly introduces the Kamenná District and its inhabitans from its inception up to the present. Here, the social transformation of the locality is highlighted, which is proven mainly by research on education and professional representation in the locality. Furthermore, the introduction briefly describes the phenomenon of gentrification and the definition of individual phases by Philip L. Clay. The primary goal of the work was to find out the public’s current opinion on the locality and thereby help to include the phenomenon of gentrification in one of the phases. The opinion of the public was ascertained using quantitative research by means of questionnaires on the Internet and in the field. The results brought the expected conclusions, the public views the Kamenná District positively and notices signs of renovation of buildings and streets, a richer cultural life or a change in the social structure of the quarter. Using the identified characteristics, gentrification was included in the third phase of its course.